Kontribusi Pendidikan terhadap Kualitas Human Capital dan Dampaknya pada Indeks Pembangunan Manusia - Delima Delima; Anisa Suci; Efri Islami Hasibuan (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Education functions as a central pillar in shaping the quality of human capital, encompassing knowledge, skills, and health, and thus plays a significant role in influencing Indonesia’s Human Development Index (HDI). This study employs a qualitative literature review by examining key theoretical frameworks in the economics of education, such as Becker’s Human Capital Theory and Schultz’s investment model, supported by relevant national empirical data. The findings indicate a very strong relationship between education and HDI improvement. This is reflected in a correlation coefficient of 0.943 between education expenditure and Indonesia’s HDI during the 2004–2023 period. The results suggest that an increase in education spending of IDR 1 trillion has the potential to raise the HDI by approximately 0.002 points. These findings confirm that investment in education not only enhances the quality of human resources but also directly contributes to sustainable national development. Despite the positive trend and the achievement of an HDI score of 75.02 in 2024, several challenges persist, particularly regional disparities, unequal access to education, and quality gaps between urban and rural areas. Therefore, more inclusive education policies, equitable access, and strengthened vocational education and training are essential to ensure that the benefits of human capital development are distributed evenly across all regions of Indonesia.